Building a better bacillus: the emergence of Mycobacterium tuberculosis - Wang, Joyce; Behr, Marcel A. (Frontiers in Microbiology, 2014)
The genus Mycobacterium is comprised of more than 150 species that reside in a wide variety of habitats. Most mycobacteria are environmental organisms that are either not associated with disease or are opportunistic pathogens that cause non-transmissible disease in immunocompromised individuals. In contrast, a small number of species, such as the tubercle bacillus, M. tuberculosis, are host-adapted pathogens for which there is no environmental reservoir. In recent years, gene disruption studies using the host-adapted pathogen have uncovered a number of “virulence factors”, yet genomic data indicate that many of these elements are present in non-pathogenic mycobacteria. This suggests that much of the genetic make-up that enables virulence in the host-adapted pathogen is already present in environmental members of the genus. In addition to these generic factors, we hypothesize that molecules elaborated exclusively by professional pathogens may be particularly implicated in the ability of M. tuberculosis to infect, persist, and cause transmissible pathology in its host species, Homo sapiens. One approach to identify these molecules is to employ comparative analysis of mycobacterial genomes, to define evolutionary events such as horizontal gene transfer (HGT) that contributed M. tuberculosis-specific genetic elements. Independent studies have now revealed the presence of HGT genes in the M. tuberculosis genome and their role in the pathogenesis of disease is the subject of ongoing investigations. Here we review these studies, focusing on the hypothesized role played by HGT loci in the emergence of M. tuberculosis from a related environmental species into a highly specialized human-adapted pathogen.